Do credit constraints amplify macroeconomic fluctuations? - Zheng Liu; Pengfei Wang; Tao Zha (Federal Reserve Bank of Atlanta, 2010)
Previous studies on financial frictions have been unable to establish the empirical significance of credit constraints in macroeconomic fluctuations. This paper argues that the muted impact of credit constraints stems from the absence of a mechanism to explain the observed persistent comovements between housing prices and business investment. We develop such a mechanism by incorporating two key features into a dynamic stochastic general equilibrium model: We identify shocks that shift the demand for collateral assets and allow productive agents to be credit-constrained. A combination of these two features enables our model to successfully generate an empirically important mechanism that amplifies and propagates macroeconomic fluctuations through credit constraints.
Keywords: E21; E27; E32; 330; credit constraints; collateral asset; housing prices; investment; financial multiplier; business cycle; structural estimation